Efeitos do agulhamento seco nos pontos-gatilho miofasciais em sujeitos com instabilidade crônica do tornozelo: ensaio clínico aleatorizado e controlado - Silva, Angela Maria Barros (2022)
Introduction: Chronic Ankle Instability (CAI) is characterized by recurrent sprains associated with self-reported joint instability. Studies show that sensorimotor deficits in CAI are related to the presence of Myofascial Trigger Points (MTPs). Dry needling of MTPs (DN-MTPs) promotes biochemical, mechanical and vascular effects, which can modify the neuromechanical disturbances of subjects with CAI. Objective: To evaluate the chronic effect of DN-MTP on Peroneus Longus (PL) and Brevis (PB) on the sensorimotor system of subjects with CAI. Method: Experimental, randomized, double-blind, Shamcontrolled study, performed with 15 subjects with CAI. All subjects underwent neuromuscular control training, however they were randomized into 2 groups: 1) Real Dry Needling - RDN: 8 subjects and 2) Sham Dry Needling - SDN: 7 subjects. Subjects were evaluated by the Cumberland Ankle Instability Tool - CAIT and Visual Analogue Scale - VAS (primary outcome) and by Infrared Thermography, Pressure Pain Threshold - PPT, Superficial Electromyography - EMG - of PL and PB, ankle evertor strength and control one-legged dynamic postural posture (secondary outcomes), at the beginning of the study (Av1), after 12 sessions (Av2) and one week after the end of treatment (Av3).Statistical analysis was performed using the Statistical Package for Social Sciences software (SPSS -20.0), applying the repeated measures ANOVA test. Results: An increase in the CAIT score and a decrease in the VAS score over time (P<0.001) were observed, with no difference between the groups, in addition to a decrease in the anteroposterior (AP) and mediolateral (ML) displacement in the RNg after the intervention and in one week (P<0.001). Conclusion: the DNMTPs of the PL and PB increased the postural control, in the AP and ML displacements, without changing the levels of PPT, EMG, muscle strength, pain perception and instability of the subjects with CAI. In addition, the MTPs of the investigated musculature did not show a thermal pattern and did not suffer temperature change over time in any of the proposed interventions.